Granular Cell Tumor of the Breast Imitating a Malignant Tumor: A Case Report and Review of Literature - Gumowska, Magdalena Ewa; Szlenk, Axana Maria; Roszkowska-Purska, Katarzyna; Piotrzkowska-Wróblewska, Hanna; Secomski, Wojciech; Dobruch-Sobczak, Katarzyna Sylwia (Archives of Clinical and Medical Case Reports, 2022)
A 22 year-old woman with no family history of breast cancer developed a painful breast tumor in the inner lower quadrant of the left breast. After surgical consultation, ultrasound examination was advised. On ultrasound, the mass demonstrated malignant features such as non-parallel orientation, hypoechogenicity, spiculated margins, posterior shadowing, peripheral vessels on color Doppler and increased stiffness in the tissue surrounding the tumor. Before biopsy, mammography was performed. The mass had higher density than fibroglandular tissue, margins were ill-defined (spiculated) and had no microcalcification. BIRADS 5 category was preassigned. Core biopsy revealed granular cell tumor (GCT). The patient is undergoing regular follow-up. Granular cell tumor is rare and generally benign, however, it typically demonstrates malignant features clinically and on obtained diagnostic images. This article highlights the variety of imaging features accompanying benign breast tumors.